Newman Error Analysis (NEA): Identifying Students’ Functional Thinking Errors Based on Self-Efficacy - Yuniati, Suci; Rizky Aulia Nisa; Annisah Kurniati; Depriwana Rahmi; Evrim Erbilgin (Hipotenusa: Journal of Mathematical Society, 2025)
This study aims to analyze the relationship between self-efficacy and high school students’ errors in functional thinking using Newman Error Analysis (NEA). This study uses a qualitative approach with a descriptive method to analyze the pattern of students’ functional thinking errors in solving mathematical problems. The subjects of the study were selected by purposive sampling based on variations in students’ self-efficacy levels (high, medium, and low) to obtain a more comprehensive representation in the analysis of functional thinking errors. Students’ self-efficacy was measured using a Likert scale-based questionnaire, while essay-based tests were used to identify their mathematical functional thinking abilities. Additional data were obtained through interviews based on interview guidelines to understand students’ functional thinking processes in solving problems. The validity of the research data was achieved using the triangulation method by comparing test result data, questionnaires and interview guidelines. The results showed that students with high and medium self-efficacy tended to make fewer functional thinking errors than students with low self-efficacy. Students with low self-efficacy made more errors in understanding problems (comprehension errors), transforming information (transformation errors), applying procedures (process skill errors), and writing final answers (encoding errors). These findings can be a basis for teachers in designing more effective learning strategies to improve understanding of the concept of function.